Men who Care: care and intergeneration relations among Portuguese families in times of austerity - Lima, Antónia (El Cuidado de Mayores y Dependientes: Avanzando hacia la Igualdad de Género y la Justicia Social., 2021)
this chapter analyses the intertwining relation between public policies, care, and emotions. Based on fieldwork carried out in Portugal it explores the impact of austerity policies on care and intergeneration relations, focusing on men who are caregivers